Phenotype and Function of CD25-Expressing B Lymphocytes Isolated from Human Umbilical Cord Blood - Sylvie Amu; Mikael Brisslert (Clinical and Developmental Immunology)
Background. We have shown that approximately 30% of human peripheral blood B-cells express CD25. B cells expressing CD25 display a mature phenotype belonging to the memory B-cell population and have a better proliferative and antigen-presenting capacity. The aim of the present study was to characterize the CD25-expressing subset of B cells in human cord blood. Material and Methods. Mononuclear cell fraction from human cord blood (n=34) and peripheral adult blood (n=22) was sorted into CD20+CD25+ and CD20+CD25- B-cell populations. Phenotype and function of these B-cell populations were compared using flow cytometry, proliferation, cytokine production, and immunoglobulin secretion. Results. CD25-expressing B cells are a limited population of cord blood mononuclear cells representing 5% of the CD20+ B cells. They are characterised by high expression of CD5 in cord blood and CD27 in adult blood. CD25-expressing B cells express a functional IL-2 receptor and high levels of CC-chemokine receptors and spontaneously produce antibodies of IgG and IgM subclass. Conclusions. CD25 expression is a common denominator of a specific immunomodulatory B-cell subset ready to proliferate upon IL-2 stimulation, possibly ready to migrate and home into the peripheral tissue for further differentiation/action.